2018
DOI: 10.1111/jonm.12626
|View full text |Cite
|
Sign up to set email alerts
|

An integrative review on conflict management styles among nursing professionals: implications for nursing management

Abstract: This integrative review provided up-to-date evidence that is useful when formulating interventions to equip nurses with positive conflict-management styles necessary to mitigate and manage conflict. Such interventions may include: structured training on conflict management, team building, and conflict coaching activities, continuing professional development, reflective exercises, simulation, and role playing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 53 publications
4
40
0
4
Order By: Relevance
“…The authors concluded that updated evidence is useful for the elaboration of interventions aimed to provide nurses with positive management styles that are necessary to reduce and manage conflicts. Such interventions may include structured training in conflict management, team building and conflict training activities, continuous professional development, reflection, simulation and role -play exercises (23) .…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that updated evidence is useful for the elaboration of interventions aimed to provide nurses with positive management styles that are necessary to reduce and manage conflicts. Such interventions may include structured training in conflict management, team building and conflict training activities, continuous professional development, reflection, simulation and role -play exercises (23) .…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve the preferred cultural transformation, nurse managers need to request top management to allocate annual funds for staff training and development. In support of Labrague et al (2018), we recommend nurse managers use coaching and promote training to help staff adopt techniques that minimize conflict and emphasize team problem-solving. Finally, building a positive professional culture based on collaborative problem-solving should be part of the mission and vision of all healthcare organizations.…”
Section: Implications For Nursing Practice and Policymentioning
confidence: 99%
“…Dalam mengelola konflik terdapat banyak faktor yang mempengaruhi seperti usia, kecerdasan emosional, lama kerja, jenis kelamin, tingkat pendidikan, pelatihan terkait manajemen konflik, jabatan manajerial dan kepribadian. Labrague, Hamdan, & Mcenroe-Petitte (2018) mendapatkan bahwa pilihan untuk mengelola konflik berkorelasi dengan variabel demografi seperti usia, jenis kelamin, lama kerja dan tingkat pendidikan. Untuk dapat meningkatkan kemampuan mengelola konflik dan menurunkan kejadian konflik di tempat kerja, perlu dilakukan identifikasi segera agar didapatkan intervensi yang tepat (Labrague et al, 2018).…”
Section: Pembahasanunclassified
“…Labrague, Hamdan, & Mcenroe-Petitte (2018) mendapatkan bahwa pilihan untuk mengelola konflik berkorelasi dengan variabel demografi seperti usia, jenis kelamin, lama kerja dan tingkat pendidikan. Untuk dapat meningkatkan kemampuan mengelola konflik dan menurunkan kejadian konflik di tempat kerja, perlu dilakukan identifikasi segera agar didapatkan intervensi yang tepat (Labrague et al, 2018). Adapun intervensi yang dapat dilakukan yaitu dengan mengembangkan pendidikan dan pelatihan interperofesional sehingga memberikan kesempatan bagi tenaga kesehatan untuk belajar bersama (Lancaster, Kolakowsky-Hayner, Kovacich, & Greer-Williams, 2015).…”
Section: Pembahasanunclassified